Research Progress on the Causes of Turbidity in Lujiu and the Treatment Measures - Wang, Yan; Chen, Pengfei; Wang, Zhongfan; Chen, Xianggui; Tandhanskul, Atittaya (Applied Science and Engineering Progress, 2026)
Lujiu is a traditional Chinese alcoholic beverage made by extracting animal and plant medicinal materials in Baijiu (Chinese liquor) or Huangjiu (Chinese rice wine). Due to the precipitation of various substances in the base liquor, Lujiu has a richer taste and higher nutritional value. However, it is also prone to turbidity. The turbidity that occurs after the preparation and storage of Lujiu seriously affects its appearance, quality and commercial value. Although there is a lot of discussion about turbidity and precipitation in wine and fruit wine, articles about the turbidity phenomenon of Lujiu are not common. This article reviews the main components in Lujiu, such as proteins, polysaccharides and phenolic substances, as well as the complex interactions between these components, and the commonly used methods for removing turbidity. This article aims to provide a basis for the future development of Lujiu products and the prevention and control of turbidity.